Oral adenosquamous carcinoma mimicking a pyogenic granuloma: A challenging diagnosis - Lima, Celina Faig; Acay, Renata [UNESP]; Anbinder, Ana Lia [UNESP]; Almeida, Janete Dias [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (FapUNIFESP (SciELO), 2016)
Adenosquamous carcinoma is an aggressive variant of squamous cell carcinoma. This report describes a case of adenosquamous carcinoma with clinical features of a benign lesion and discusses the differential diagnoses, especially regarding histopathological and immunohistochemical analyses. A 45-year-old male was referred to our outpatient clinic complaining about a rapid-growing enlargement in hard palate. Clinical examination revealed an erythematous and pedunculated nodule with lobulated non-ulcerated surface. Excisional biopsy was performed following clinical diagnosis of pyogenic granuloma. Histologically, the specimen consisted of areas characterizing both welldifferentiated squamous cell carcinoma and true adenocarcinoma. After a broad list of immunohistochemical markers was evaluated (AE1/AE3, CEA, CK5, CK7, CK8/18, p53, p63 and Ki67), the diagnosis of adenosquamous carcinoma was rendered and the patient referred to complementary surgery. Adenosquamous carcinoma represents a challenge in diagnostic routine due to its rarity, diverse range of clinical presentations and histological features. Furthermore, classical clinical benign features may be present in malignant lesions; hence the submission of every surgical specimen to histological analysis is mandatory to provide the patient the adequate treatment.
Keywords: Adenosquamous carcinoma; Immunohistochemistry; Mouth mucosa; Squamous cell carcinoma